Digital Knowledge, Skills, and Ethics for Elementary School Students in the Artificial Intelligence Era - Romadhon, Muhammad Syahru (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study aims to analyze the implementation of digital among students at Madrasah Ibtidaiyah (Islamic elementary school) by considering three principal aspects: knowledge, skills, and attitudes. The research employs a qualitative literature review that integrates digital ethics theory with Islamic values. The findings indicate that (1) an understanding of digital ethics enhances awareness of tawhid and instills a sense of moral responsibility in the use of technology; (2) skills related to digital ethics promote appropriate conduct, accountability, and balance in online interactions; and (3) attitudes toward digital ethics cultivate akhlaq al-karimah and muraqabah, which serve as manifestations of spiritual awareness in the digital sphere. These results suggest that education grounded in Islamic digital ethics can develop students who are both digitally literate and morally conscientious. Consequently, Madrasah Ibtidaiyah plays a vital role in fostering moral responsibility, moderation, and self-awareness in the utilization of technology.